Association of trabecular bone score corrected for tissue thickness with glucose metabolism in acromegaly - Kužma, Martin; Vaňuga, Peter; Pávai, Dušan; Killinger, Zdenko; Hans, Didier; Binkley, Neil; Payer, Juraj; Jackuliak, Peter (Frontiers in Endocrinology, 2024)
Introduction Acromegaly is associated with increased vertebral fracture (VF) risk regardless of bone mineral density (BMD). However, the vertebral trabecular compartment is still low; a possible contributor to this may be impaired glucose metabolism (GM) which frequently complicates acromegaly. Additionally, soft tissue thickness may confound bone imaging in acromegaly patients. Objective This study aims to assess the association of GM with BMD, trabecular bone score adjusted for BMI (TBSBMI), and trabecular bone score adjusted for tissue thickness (TBSTT) among acromegaly subjects. Patients and methods A cross-sectional study was performed among 70 consecutive acromegaly patients (24 male/46 female, aged 55.1 years) divided in two subgroups: abnormal GM (n = 35) and normal GM (n = 35). Using DXA, BMD, TBSBMI, TBSTT, and VF screening were performed. Results In all subjects, TBSTT was higher (mean 9.5%) than TBSBMI. Abnormal GM subjects had lower TBSBMI (1.166 ± 0.15) than normal GM subjects (1.232 ± 0.12; p < 0.05). No between-group difference in TBSTT or BMD was observed. In a multiple regression model, the best predictor of TBSTT was HbA1c (p = 0.002). None of the DXA measures or GM parameters was a significant predictor of VF (n = 7). Conclusion The abnormal GM acromegaly subjects had lower TBSBMI than those with normal GM. TBSTT was higher than TBSBMI, and no between-group difference based on GM status was observed. TBSTT was significantly associated with GM parameters, notably HbA1c. The relationship of TBSTT with GM parameters may imply an effect of GM on trabecular bone microstructure in patients with acromegaly; a further study is indicated.